Poly[dinitrato[μ3-2,4,6-tris(4-pyridyl)-1,3,5-triazine]cobalt(II)] - Ya-Ping Wang; Ning Zhang; Xiang He; Min Shao; Ming-Xing Li (Acta Crystallographica Section E, 2011)
The solvothermal reaction of Co(NO3)2 and 2,4,6-tris(4-pyridyl)-1,3,5-triazine in dimethylformamide/ethanol mixed solvent afforded the title coordination polymer, [Co(NO3)2(C18H12N6)]n, in which the CoII atom is seven-coordinated by pyridyl groups of three different ligands and two chelating nitrate anions. The complex displays a nano-sized porous metal–organic framework that belongs to a (10,3) topological network.